A new detection device for decomposition products of insulating gas in electrical equipment. Issue 1 (March 2021) - Fang, Chongfeng; Xu, Yi; Ma, Yao; Peng, Bo; Wang, Yu; Xia, Ji; Chen, Jingzhe; Lin, Xin
Abstract: In this paper, a multi-functional SF6 gas decomposition products comprehensive analysis device is realized by using spectral absorption technology, integrating the existing electrochemical sensor technology, and integrating a variety of detection modules. In this paper, a set of hardware system is researched and implemented, which takes microprocessor as the control core and touch LCD as the human-machine interface to realize the SF6 Electrical Equipment multi-functional gas analysis equipment.